Anti-bacterial effects of seagrass Syringodium isoetifolium against some common wound bacteria. - Ramos, Gabrielle Thea I. (2019.)
Some seagrass species have been found to contain bioactive compounds with antimicrobial properties that can be broad spectrum or highly specific. In light of the continuing global threat of antibiotic resistance, this study aims to contribute efforts of screening fro bioactive compounds in marine resources that can lead to drug discovery and development. It specifically targets the seagrass Syringodium isoetifolium population in Tando, Guimaras and evaluated its antimicrobial properties against strong wound pathogens: Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeuriginosa, and Escherichia coli. It further compares the potential anti-fouling capability of S. isoetifolium relative to other seagrass species using epiphyte load as indicator. Ethanol crude extract reveals significant antibacterial activity against the four bacterial strains tested but showed a higher antibacterial activity against gram negative bacteria strains Pseudonomas aeruginosa and Escherichia coli. The ethanol crude extract also gave a larger zone of inhibition compare to the result of acetone and methanol crude extracts as presented by Mani et al. Visual epiphyte load was observed to decrease by depth with the least load observed on S. isoetifolium. This leads to the hypothesis of a higher production and more effective antifouling and antibacterial metabolites by the target species
Special Problem (Undergraduate, Bachelor of Science (Biology)) College of Artys and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Seagrassess; Syringodium isoetifolium